The individual experience of ageing prisoners: systematic review and meta-synthesis through a Good Lives Model framework - Di Lorito, Claudio; Völlm, Birgit; Dening, Tom (Wiley, 2018)
Objective: The existing literature on ageing prisoners tends to focus on such aspects as diagnosis and physical ill-health. In contrast, the experience of imprisonment from the perspective of ageing prisoners has received less attention. Grounded in a Good Lives Model theoretical framework, we reviewed and meta-synthesised literature around their experience of life in prison, its impact on their wellbeing and how prison services are currently addressing their complex needs. We further identify potential areas of improvement. Methods: 1. Systematic search on Assia, PsycInfo, MedLine, Embase, Web of Science, Google and Gov.uk. 2. Extraction and categorisation of data on NVivo. 3. Development of themes through thematic analysis and meta-synthesis. 4. Identification of potential areas of improvement. Results: We selected 25 studies for our review, of which thirteen were from the USA, seven from the UK, two from Australia and one each from Ireland, Switzerland and Israel. We identified three themes: The hardship of imprisonment, addressing health and social care needs, and the route out of prison. Conclusions: Ageing prisoners have unique and complex health and social care needs which, to varying degree across different countries, are mostly unmet. Promising initiatives to address their needs are emerging but, at present time, the overall experience of incarceration for the ageing prisoner is quite poor, given the inconsistent physical, emotional and social care support offered from prison intake to release and beyond.